Dossier I: La participación ciudadana como base para la disminución de la violencia en México - Sarwat Hikal-Carreón, Wael (Quadernos de criminología, 2020)
With the start of a new federal and other public administration, sometimes certain groups of the population expect the problems that Mexico has been dragging on for years will be solved in a couple of days. Many of the conflicts and difficulties that the country is going through do not have a paternalistic vertical solution from above, but with the action and commitment of all citizens. An important part of this is also understanding the criminal phenomenon through studies in the field, an informed population has better tools to reflect situations and from the individual, change and be an actor of social change.